Characterization of calibration curves and energy dependence GafChromicTM XR‐QA2 model based radiochromic film dosimetry system. Issue 6 (29th May 2014) - Tomic, Nada; Quintero, Chrystian; Whiting, Bruce R.; Aldelaijan, Saad; Bekerat, Hamed; Liang, LiHeng; DeBlois, François; Seuntjens, Jan; Devic, Slobodan
Abstract : Purpose: The authors investigated the energy response of XR‐QA2 GafChromic TM film over a broad energy range used in diagnostic radiology examinations. The authors also made an assessment of the most suitable functions for both reference and relative dose measurements. Methods: Pieces of XR‐QA2 film were irradiated to nine different values of air kerma in air, following reference calibration of a number of beam qualities ranging in HVLs from 0.16 to 8.25 mm Al, which corresponds to effective energy range from 12.7 keV to 56.3 keV. For each beam quality, the authors tested three functional forms (rational, linear exponential, and power) to assess the most suitable function by fitting the delivered air kerma in air as a function of film response in terms of reflectance change. The authors also introduced and tested a new parameter χ = net Δ R ·e m netΔ R that linearizes the inherently nonlinear response of the film. Results: The authors have found that in the energy range investigated, the response of the XR‐QA2 based radiochromic film dosimetry system ranges from 0.222 to 0.420 in terms of netΔ R at K air air = 8 cGy. For beam qualities commonly used in CT scanners (4.03–8.25 mm Al), the variation in film response (netΔ R at K air air = 8 cGy) amounts to ± 5%, while variation in K air air amounts to ± 14%. Conclusions: Results of our investigation revealed that the use of XR‐QA2 GafChromic TM film is accompanied by a rather pronounced energy dependent response for beam qualities used for x‐ray based diagnostic imaging purposes. The authors also found that the most appropriate function for the reference radiochromic film dosimetry would be the power function, while for the relative dosimetry one may use the exponential response function that can be easily linearized.